Strategi Humas Polisi Daerah (POLDA) Sumatra Barat Dalam Pelayanan Informasi Penerimaan Anggota Kepolisian Negara Republik Indonesia (POLRI) - Mulyadi, Yandra; Darwis, Yuliandre (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Recruitment of National Police Members is a routine activity carried out by the National Police of the Republic of Indonesia (Polri) every year, this activity aims to obtain quality and highly integrated Human Resources (HR), in order to strengthen and improve the performance of the National Police in order to protect and maintain security. and public order (Harkamtibmas). The National Police has a tough task ahead, therefore young people are needed as the nation's successors to serve as state servants to answer all the challenges currently faced by the National Police. Currently, the needs of National Police Members according to the List of Personnel Composition (DSP) are far inversely proportional to the actual number of National Police Members in the field. Because it refers to existing conditions and situations, it is necessary to change the system, number and competency in recruiting Polri members whose presence is really needed by the community. Therefore, it is necessary to increase the quantity and quality of Polri members who can carry out their main duties as state servants optimally by fulfilling the Ideal Polri Member. The success of the National Police both in performance and as Harkamtibmas cannot be separated from the duties of a publicist in documenting every activity carried out by members of the National Police and publishing media so that it can be seen and felt directly by the public, even Public Relations as the front guard of the National Police in providing information services to the public both in terms of directly or through the media, such as in the recruitment of new members of the National Police, brilliant strategies are needed from a Public Relations person to provide information to the wider community, so that it is easier for the public to get the information they need.